DEVELOPMENT OF THE MODELS OF “PRODUCERS – PRODUCTS – CONSUMERS” GENERALIZED SYSTEMS - Borovska, Taisiya; Kolesnik, Irina; Severilov, Victor; Mihaylova, Inna (Scientific Works of Vinnytsia National Technical University, 2015)
The system of working models of “producers – products – consumers” distributed system has been constructed. In the model the behaviour of each separate consumer, of a consumer and a retailer is simulated. Investigations were conducted using the models. New results for direct evaluation of the risks are obtained.